2022
DOI: 10.1177/01461672221125619
|View full text |Cite
|
Sign up to set email alerts
|

The Equality Paradox: Gender Equality Intensifies Male Advantages in Adolescent Subjective Well-Being

Abstract: Individuals’ subjective well-being (SWB) is an important marker of development and social progress. As psychological health issues often begin during adolescence, understanding the factors that enhance SWB among adolescents is critical to devising preventive interventions. However, little is known about how institutional contexts contribute to adolescent SWB. Using Programme for International Student Assessment (PISA) 2015 and 2018 data from 78 countries ( N = 941,475), we find that gender gaps in adolescents’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…Expressed differently, boys are more satisfied than girls with their life. Remarkably, it was recently demonstrated that this gender gap is wider in more gender-equal countries (Campbell et al, 2021;Guo et al, 2022). Gender equality is presumably about giving women the same privileges and opportunities as men.…”
Section: Introductionmentioning
confidence: 99%
“…Expressed differently, boys are more satisfied than girls with their life. Remarkably, it was recently demonstrated that this gender gap is wider in more gender-equal countries (Campbell et al, 2021;Guo et al, 2022). Gender equality is presumably about giving women the same privileges and opportunities as men.…”
Section: Introductionmentioning
confidence: 99%
“…The disparity between our results, in which men and women are considered separately, and previous claims about a gender-equality paradox and its overarching theoretical implications are striking. We do acknowledge that not all previous studies have ignored these slopes (e.g., Guo et al, 2022;Schmitt et al, 2008;Walter et al, 2020), but those that have found strong support for the gender-equality paradox have all done so. The variety of approaches to assessing the gender-equality paradox has made it difficult to provide state-of-the-art summaries of the current knowledge of the topic.…”
Section: The Contribution Of Our Results To Current Knowledge Of the ...mentioning
confidence: 86%
“…The commonly used difference score correlation is not equivalent to a standardized effect size of slope non-parallelism. Even studies that have examined the slopes for men and women separately (e.g., Guo et al, 2022;Schmitt et al, 2008;Walter et al, 2020) have often relied on difference score correlations as estimates of effect size or reported on unstandardized effect sizes. In a direct difference score prediction, rX,Y1-Y2, the nonparallelism between rX,Y1 and rX,Y2 is standardized using the standard deviation of the difference score (SDY1-Y2).…”
Section: Quantifying Effect Size In the Gender Gap Predictionsmentioning
confidence: 99%
“…Moreover, it has been suggested that girls are exposed to earlier sexualization and greater body objectification, which have been associated with depressive symptoms [ 87 ]. As Finland has been ranked as having high levels of gender equality [ 88 ], our findings on gender differences could also be linked to the equality paradox of health, suggesting that individuals living in countries with greater levels of gender equality report larger gender gaps in health outcomes favoring boys [ 89 ]. However, it is also possible that poor mental health among boys is manifested in other ways not measured in our study, such as increased anti-social behaviors and substance use [ 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%